Medicines information in medical journal advertising in Australia, Malaysia and the United States: A comparative cross-sectional study - Othman, Noordin; Vitry, Agnes I.; Roughead, Elizabeth E. (University of Auckland, 2010)
Objective: The aim of this study was to compare the provision of medicines information in medical journal advertising in Australia,Malaysia and the United States.